The Effects of Fire on Organic Functional Groups of Peat in Relation to Water Content - Said Ramadhan; Fadly Hairannoor Yusran; Abdul Haris; Suhaili Asmawi (UNIVERSITY OF LAMPUNG, 2014)
The aim of this research was to study the decline of organic functional group through the process of burning in peat. In addition, this study was also to examine the relationship between water content in peat and organic functional group after combustion (burning). Peat drying was conducted in an oven at a temperature of 75°C with the interval of 0, 1, 2, 3, 4, 5 and 6 hours. Each time interval had three replicates within two sets of experiments so that the total number of samples were 42 (experimental units). Variables measured were moisture content, total acidity, COOH groups, and OH-phenolate. The relationship between the water content with total acidity, COOH groups and OH-phenolate were determined by the equation y = bx + a. The results showed that the relationship between the water content with organic functional group was linear. While the relationship between peat water content with organic functional group after burning was irregular, although water levels through the process of burning have been greatly reduced. Keywords: Burning peat; organic functional groups; water content [How to Cite: Said R, FH Yusran, A Haris and S Asmawi. 2014. The Effects of Fire on Organic Functional Groups of Peat in Relation to Water Content. J Trop Soils 19: 143-149. Doi: 10.5400/jts.2014.19.3.143]